Sexuality and reproduction: implications in the process of healthy adolescence - Araújo, Adelita Campos; Lunardi, Valeria Lerch; Silveira, Rosemary Silva da; Thofehrn, Maira Buss; Porto, Adrize Rutz; Soares, Deisi Cardoso (Rev Rene, 2012)
This study aimed to understand the perceptions of adolescents about their process of healthy adolescence with regard to sexuality and reproduction. This is a qualitative research of exploratory type, involving 10 teenagers, in a state school in southern Rio Grande do Sul, between August and October 2007. To collect the data, were used semi-structured interviews, whose contents were subjected to thematic analysis, emerging the theme: sexuality and reproduction in adolescence. At the data, it was noticed the need to provide more guidelines to a healthy adolescence, in the sense of strengthening and promoting the necessary security for the exercise of adolescent sexuality and reproduction. It also showed the need to prepare the adolescent by professionals of health, of education or the family, to face some situations, such as: unwanted pregnancy, first sexual intercourse, self-medication, fear of talking to parents about sexuality and reproduction, among others.